ChemInform Abstract: Alternative Synthetic Route to Annulated Diaminopyrimidines. Issue 52 (29th December 2014) - Erdmann, Alexandre; Halby, Ludovic; Cantagrel, Frederic; Sautel, Francois; Massiot, Georges; Arimondo, Paola B.
Abstract Annulated diaminopyrimidines are prepared via Thorpe—Ziegler cyclization of various dinitriles followed by in situ reaction with cyanamides (II) in a one‐pot manner.